The Effect of Work Environment, Comperency Development and Leadership Style on Employee Job Satisfaction in The Bali Tourisme Industry - Hakim, Chairul (West Science Business and Management, 2024)
This research is conducted to study the influence of work environment, commitment development, and leadership style on employee job satisfaction in the Bali tourism industry. In this research, a quantitative approach was adopted, where the sample of employees totaled 125 and the measuring instrument used was a Likert scale ranging from 1 to 5. The data analysis used in this study is SEM-PLS 3. These findings thus prove that work environment, commitment development, and leadership style are the factors contributing to employees' job satisfaction and commitment. It is therefore suggested that enhancement in the work environment and development of commitment, together with effective leadership styles, plays an important role in improving employee satisfaction within the tourism sector in Bali. These insights shall serve useful for the leaders in the tourism sector in an effort towards engaging employees better and improving organizational performance through reduced turnover.